On Generalized Regular Local Ring - Ibraheem, Zubayda M.; Shereef, Naeema A. (Science Journal of University of Zakho, 2015)
A ring R is called a generalized Von Neumann regular local ring (GVNL-ring) if for any a∈R, either a or (1-a) is π-regular element. In this paper, we give some characterization and properties of generalized regular local rings. And we studied the relation between generalized regular local rings, Von Neumann regular rings, Von Neumann regular local rings (VNL-rings) and exchange rings.